Aktivitas Aantioksidan Kombinasi Daun Sirsak (Anonna Muricata L.) dan Daun Beluntas (Pluchea Indica L.) - hasanah, ulfatun; Inayah, Nurul (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2023)
Soursop (Anonna Muricata L.) and Beluntas (Pluchea indica L.) are plants that contain secondary metabolites that have potential as antioxidants. The purpose of this study was to determine the activity of soursop leaf samples, beluntas and their combination in reducing DPPH. Samples were made into powder followed by maceration and evaporated the solvent to become an extract. Antioxidant activity testing with DPPH silencing method with UV-Vis spectrophotometer. Antioxidant activity test results for soursop leaf samples, beluntas, combinations (1:1), (1:2) and (2:1) have IC50 values of 58, 51, 57, 61 and 68 ppm, respectively. Further analysis Combination index of the combination (1:1) has a synergistic effect and the combination (1:2) and (2:1) has an antagonistic effect. Keywords: Antioxidant Activity, Anonna Muricata L. leaf, Pluchea indica L. leaf, DPPH